The effects of mindfulness enhanced Tai Chi Chuan training on mental and physical health among beginners: a randomized controlled trial - Qu, Ping; Zhu, Xiaoqing; Zhou, Hui; Kang, Zhengyu; Li, Ran; Wen, Jingsi; Pan, Feng; Liu, Yang; Zhu, Ting; Cao, Qian; Wang, Xiaoyan; Wang, Yuyin (Frontiers in Psychology, 2024)
Introduction: Tai Chi Chuan (TCC) is a traditional Chinese mind-body exercise widely adopted in Chinese communities and colleges. However, the mindful essence of TCC is rarely emphasized during popularization. This makes it difficult for beginners to benefit from it. The present study aimed to examine the effects of a Mindfulness-enhanced Tai Chi Chuan (MTCC) intervention, which enhances mindfulness components embedded within TCC, on mental and physical health among beginners.Methods: A randomized controlled trial was conducted with 119 healthy college students new to Tai Chi Chuan training. Participants were assigned to either the MTCC group or the TCC group. Both interventions consisted of 10 weekly 90-minute training sessions, with the MTCC group emphasizing and enhancing mindfulness components. Outcome measures included mindfulness, depression, anxiety, stress, and physical fitness, assessed at baseline and post-intervention.The results showed that the MTCC group had significantly greater improvements than the TCC group in mindfulness, anxiety, stress, and health-and skill-related physical fitness. There were no significant differences between the two groups in depression.The findings suggest that compared to TCC, MTCC can effectively promote individuals' physical fitness and provide additional benefits to mental well-being. MTCC can be recommended as an accessible and beneficial intervention for beginners to improve mental health and strengthen their bodies.Clinical review registration: https://www.chictr.org.cn/, identifier ChiCTR2200058175.